Medlemmarnas syn på lantbrukskooperativa företag - Friis, Anna (SLU/Dept. of Economics, 2011)

(untitled)
During the last decade several cooperatives have struggled against many problems. Especially in North America several cooperatives have been forced to reconstruct, merge or have been purchased by other firms. There are many reasons behind these problems, but one observation made on these cooperatives implies that they have one thing in common. The cooperatives are all very large and have a complex business structure. Lantmännen is one of the largest cooperatives in the Nordic Countries with its main office in Sweden. In Nilsson et al. (2009) there are observations made that the issues Lantmännen are struggling against occur from the fact that it has a large and complex organization structure. Due to the large and complex organization Lantmännen´s members have a low amount of trust in the board of directors. This study aims to compare member trust between three Swedish cooperatives in the grain business. The three cooperatives are Lantmännen, Varaslättens Lagerhus Ek. Förening from Västergötland and Södra Åby Lokalförening from Skåne. Västergötland is a province in the south west of Sweden, and Skåne is a province in the southern of Sweden. These cooperatives have the same core business with grain handling and sales of farm inputs. They are, however, very different in terms of the number of members, the amount of vertical and horizontal integration and size of the collective capital. Lantmännen has 36 000 members and has operations in 18 counties. Varaslättens Lagerhusförening has around 1 500 members and it has its business in Västergötland. Södra Åby is the smallest cooperative with around 165 members and its operations are in the south of Skåne. In order to realize this study a survey had to take place. Questionnaires have been sent to the members of Varaslättens Lagerhusförening and Södra Åby Lokalförening. Data had already been collected from the members of Lantmännen in another study (Kihlén 2007). The response rate was over 70 percent from both cooperatives. This must be considered as very good. The data indicates that the members of Lantmännen have lower trust to their board of directors and the members are not satisfied with the cooperative’s business. The members of the smaller cooperatives are much more satisfied with their cooperative, and have more trust to their board of directors. The members of the smaller cooperatives think it is very easy to get contact with the board of directors, and they are also very committed to their cooperative. In general the members of the smaller cooperatives have a larger ownership feeling towards their cooperative.